Establishment and Characterization of a Novel Rat Model of Mechanical Low Back Pain Using Behavioral, Pharmacologic and Histologic Methods - Muralidharan, Arjun; Park, Thomas S. W.; Mackie, John T.; Gimenez, Luiz G. S.; Kuo, Andy; Nicholson, Janet R.; Corradini, Laura; Smith, Maree T. (Frontiers in Pharmacology, 2017)
Chronic low back pain (LBP), the leading cause of disability globally, is notoriously difficult to treat. Most rodent models of LBP mimic lumbar radicular pain rather than mechanical LBP. Here, we describe establishment of a new rat model of mechanical LBP that is devoid of a neuropathic component. Groups of adult male Sprague Dawley rats were anesthetized and their lumbar L4/L5 and L5/L6 intervertebral discs (IVDs) were punctured (0.5mm outer diameter, 2mm-deep) 5 (LPB-5X) or 10 (LBP-10X) times per disc. Sham-rats underwent similar surgery, but without disc puncture. Baseline noxious pressure hyperalgesia of lumbar axial deep tissues, mechanical allodynia in the hindpaws and gait were assessed prior to surgery and once-weekly until study completion on day 49. The model was also characterized using pharmacologic and histologic methods. Good animal health was maintained for 49 days post-surgery. For LBP- but not sham-rats, there was temporal development of noxious pressure hyperalgesia in lumbar axial deep tissues at days 14 – 49 post-surgery. Importantly, there were no between-group differences in von Frey paw withdrawal thresholds or gait parameters until study completion. On day 49, significant histologic changes were observed in the L4/L5 and L5/L6 IVDs for LBP-10X rats, but not sham-rats. In LBP-10X rats, single bolus doses of morphine produced dose-dependent relief of primary and secondary mechanical hyperalgesia in lumbar axial deep tissues at L4/L5 and L1 respectively. In conclusion, our new rat model has considerable potential for providing novel insight on the pathobiology of mechanical LBP and for analgesic efficacy assessment of novel compounds.